Comparative ecology of vascular plant, bryophyte and testate amoeba communities in four Sphagnum peatlands along an altitudinal gradient in Switzerland - Koenig, Isabelle; Feldmeyer-Christe, Elizabeth; Mitchell, Edward (My University, 2015)
Monitoring tools are needed to assess changes in peatland biotic communities and ecosystem functions inresponse to on-going climate and other environmental changes. Although the responses of soil organismsand plants to ecological gradients and perturbations do not always correlate, peatland monitoring ismainly based on vegetation surveys. Testate amoebae, a group of protists, are important contributorsto carbon and nitrogen cycling in organic soils and are useful bioindicators in peatland ecology andpaleoecology. There is however little comparative data on the value of testate amoebae, vascular plantsand bryophytes as bioindicators of micro-environmental gradients in peatlands.We compared the relationships of testate amoebae, bryophytes, and vascular plants with soil tempera-ture, water table depth, micro-habitats and the carbon and nitrogen content of Sphagnum mosses in fourpeatlands along a 1300 m altitudinal gradient in Switzerland. We used the full diversity of vascular plantsand bryophyte but only a selection of ten easily identifiable testate amoeba morpho-taxa (i.e. species orspecies-complexes).Indirect and direct gradient ordinations, multiple factor analysis (MFA) and transfer function modelsfor inferring water table depth showed that a selection of ten testate amoeba taxa are more powerful (%variance explained in RDA) and accurate (discrimination among habitats) indicators of local conditions(micro-habitat type, water table depth and Sphagnum C/N ratio) than the vegetation (vascular plants andbryophytes either individually or combined and considering the full diversity).Our study showed that a limited list of ten easily identifiable testate amoeba taxa have higher bioindi-cation value than the full bryophytes and vascular plants. Furthermore, testate amoebae can be analyzedon samples collected at any season (accessibility allowing and if precise sampling sites are well marked)– a clear advantage for biomonitoring and can be used to infer past changes from the peat record at thesame taxonomic resolution. This simple approach could therefore be very useful for biomonitoring ofpeatlands.
Keywords: Peatland ecology; Bioindication; Testate amoebae; Vascular plants; Bryophytes; Community ecology; Elevation gradient